(untitled) (Nepalese Journal of Radiology, 2013)
Ganglioneuroblastoma is a tumor of the sympathetic nervous system in paediatric age group that is intermediate in behavior between ganglioneuroma and neuroblastoma. We present a case of a 3 year old girl who presented with a large long standing abdominal mass. Ultrasonographic features were suggestive of large retroperitoneal mass with calcific foci & extensive vascular encasement consistent with neurogenic tumor. Contrast enhanced computed tomography (CT) performed for staging confirmed these findings while histopathologic diagnosis of ganglioneuroblastoma was achieved by ultrasound guided biopsy. While vascular encasement is known in ganglioneuroblastoma, the scale of vascular encasement in this case is extensive. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 72-75 DOI: http://dx.doi.org/10.3126/njr.v2i2.7690